Ocena pogojev za uveljavitev modela celodnevne osnovne šole - Tinta, Andreja (Revija za elementarno izobraževanje, 2015)
Assessment of the Conditions for Introducing the All-Day Model in Basic Schools. The results of the PISA 2000 prompted the German school authorities to extend the network of all-day schools and already the results of the PISA 2012 research showed good students results justify the actions in the direction of designing a quality educational system in Germany. So, we wondered, whether Slovenian basic schools meet the conditions for the introduction of the full-day model. We carried out a non-experimental survey on a sample of headteachers who were asked to assess the spatial and personnel conditions for the implementation of the all-day basic school. In doing so, we paid attention to the differences in terms of the stratum and the number of students. The survey showed that, regardless of the stratum and the number of pupils, most of the schools met the relevant conditions. The schools in which these have not been met yet, could assure them with minimum financial investment.
Keywords: all-day basic schoo; personnel and spatial conditions; heads of basic schools